NEOPLASIA MAMÁRIA EM CADELA - Guarda Lara, Nadini De Oliveira; Da Cruz, Fernando Silvério Ferreira (Salão do Conhecimento, 2018)
Projeto de pesquisa realizado no curso de Medicina Veterinária da Unijuí